A Closed-form Energy Model for Multi-Rotors Based on the Dynamic of the Movement - Marins, João; Cabreira, Tauã; Kappel, Kristofer S.; Ferreira Jr, Paulo Roberto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2018: Anais do VIII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2018)
An energy model for a quadcopter based on the dynamic of the movement and on the Physics principles of superposition and energy conservation is proposed here. Its accuracy was checked against another model published recently in the literature, which is based on experiments carried on specifically for that purpose. The model fits the experimental data and can be easily extended for other types of multi-rotors because is a function of quadcopter parameters. More than that, as it is based only on the dynamic of the movement equations, it is differentiable and integrable, and can be applied even to gasoline-powered drone, provide that we know the efficiencies of the combustion motors. It was also studied which simplifications are allowed without compromising its accuracy, for instance, drag effects. The model confirms that there is an optimal velocity for different flight path lengths and allows to calculate that velocity. Finally, the model was used to calculate the energy consumption during a real flight with a good result and it was also applied to obtain accurate results related to energy consumption during turning maneuvers.